STUDI KOMPARASI TINGKAT KEBISINGAN PADA WAKTU BERBEDA DI SEKOLAH DASAR NEGERI MELAYU 2 BANJARMASIN - Agus Dian Mawardi; Saidah Tunnoor (Jurnal Terapung : Ilmu - Ilmu Sosial, 2020)
The research objective was to determine the Noise Level and the Difference in Noise Level at Different Times in SDN Melayu 2 Banjarmasin. The object of research is "noise levels at different times". The sampling technique used purposive sampling. The sample in this study is a classroom. The research variable consisted of the X variable, namely the time of measurement, namely 08.00, 10.00 Wite, and 12.00 WIB. The variable Y is the noise level at each measurement time. Comparative study using the one-way ANOVA approach or the F-test (Fisher Test) assisted by the application of SPSS version 23. The results of the study were significant differences at different noise levels at 08.00, 10.00, and 12.00 Wite. Generally, the noise level at SDN Melayu 2 Banjarmasin has passed the 55 dB threshold. The highest level of noise occurred at 08.00 Wite with an average of 66.26 dB, followed at 10.00 Wite with an average of 62.79 dB, and the lowest at 12.00 Wite with an average value of 60.36 dB.